WOW..

T(3,1) = T(2,T(3,0))

T(3,0) = T(2,1) = T(1,T(2,0))

T(2,0)= T(1,1) = T(0,T(1,0)) = T(0,2) = 3 (since T(1,0)=T(0,1)=2)

Now, T(3,0)= T(2,1)=T(1,3) = 5

Therefore, T(3,1)= T(2,5)

T(2,5)=T(1,T(2,4))

T(2,4)=T(1,T(2,3))

T(2,3)=T(1,T(2,2))

T(2,2)=T(1,T(2,1))= T(1,5).** There is a pattern which I got while solving which is value of T(1,x)= x+2 i.e T(1,0)=0+2=2, T(1,3) = 3+2 =5**

Using this..T(2,2)= T(1,5)=5+2=7

T(2,3)=T(1,7)=9 and T(2,4)=T(1,9)=11 and T(2,5)=T(1,11) = 13

Since T(3,1)= T(2,5)

Therefore, **T(3,1)=13**